Análisis de la diversidad genética de papas nativas (Solanum sec. Petota) de la comunidad de Chahuaytire, integrante del Parque de la Papa (Pisaq-Cusco), y de las papas nativas repatriadas por el Centro Internacional de la Papa usando marcadores microsatélites - Rojas, P. (Universidad Nacional Mayor de San Marcos, 2007)
195 native potato cultivars collected in Chahuaytire community and 246 native potatoes repatriated to Potato Park Communities Association (ACPDP) by the International Potato Center (CIP) were characterized using nine primer pairs that amplify the ten most polymorphic microsatellite loci from the potato genetic identification kit (STM0019, STPoAc58, STM0037, STM0030, STM1104, STM1052, STM1106, STM2013, STM2022), located in 9 of the 12 chromosomes of potato. The molecular characterization differentiated the 93.33% of the native potatoes from the Chahuaytire community and the 92.68% of repatriated native potatoes from CIP. 114 and 130 alleles and average diversity index between 0.762 and 0.776 were obtained in the Chahuaytire community and the repatriated potatoes, respectively. The clustering of potato cultivars was performed using the UPGMA (Unweighted Pair Group Method with Arithmetic mean) method applied to similarity matrix obtained with Jaccard coefficient. Clustering analysis revealed that no differentiation according to origin was found. Similarly, Analysis of Molecular Variance (AMOVA) revealed that the molecular variation between evaluated groups was 0.73% (p- value=0.05), indicating a basically similar genetic constitution between both groups. The main source of molecular variation, 99.27% (p-value=0.05), was found within the native potatoes inside groups. However, the finding of 6 private alleles in the native potatoes from Chahuaytire suggests that some genetic diversity maintained in the Chahuaytire native potatoes is not represented in the 246 repatriated potatoes from CIP.